"Doing" and "Undoing" Gender: The Meaning and Division of Housework in Same‐Sex Couples. Issue 2 (3rd June 2013) - Goldberg, Abbie E.
<x xml:space="preserve">Abstract</x> Research on same‐sex couples and housework can add nuance to our understanding of gender and housework. This analytic review highlights what can be gained from research on same‐sex couples and housework. Specifically, this review reveals how same‐sex couples both "do" and "undo" gender through housework. It illustrates how partners in same‐sex couples are influenced by heteronormative meaning systems surrounding housework, yet it also points to ways housework can be redefined in the context of same‐sex couples. For example, same‐sex couples who enact arrangements with more specialized divisions of labor tend to reject the notion that their labor arrangements are imitative or derivative of those of heterosexual couples. Instead, they interpret their arrangements as pragmatic and chosen, as well as uniquely defined by the fact that they are enacted in a same‐sex relational context. This review also underscores the need to attend to the social and temporal contexts that shape how same‐sex couples give meaning to and enact housework. Finally, this review challenges us to think beyond simplistic classification systems of housework as feminine or masculine, or as gendered or nongendered, and, likewise, to move beyond characterizations of same‐sex couples as either "doing" or "undoing" gender.